The legal frameworks for protecting the rights to image publication in Saudi and Sudanese journalism: Expounding the views of stakeholders - Elamin, Aisha Mohamed Ismail (Research Journal in Advanced Humanities, 2023)
The protection of people' rights in the use of their photos in journalism publishing has been thoroughly examined in this research, with press freedom to access public data repository resources taken into account. Participants in the research were chosen from a cross-section of sectors in Sudan and Saudi Arabia. A total of 832 participants from a seven stakeholder groups in the two nations made up the sample. In Saudi Arabia, 56.85% (473) of the sample came from the six designated stakeholder groups (photojournalists, media editors, staff of governmental agencies, legal experts), whereas in Sudan, 43.15% (359) participated. Using relevant statistical tools, the study made key findings. According to the findings, approximately 50% of Saudi stakeholders and 86% Sudanese participants don't think that consent is required from people before their pictures are utilised in journalistic works. Over 81% of respondents from both Sudan and Saudi Arabia agree that protecting citizens' rights should be done in accordance with the legal framework of the country, but that journalists should be free to use digital resources in their publications. More than 80% of respondents agreed that photojournalists should put the public interest first while taking and publishing photos. It is thus concluded that state authorities must establish legal and ethical norms outlining the duties and obligations of photojournalists. Important considerations like privacy invasion, user permission, and public safety should all be baked into these rules.